A novel axial reluctance resolver proposal and its winding configuration optimization using winding function method. (November 2022) - Ran, Xiaohe; Zhao, Meng; Shang, Jing
Abstract: The analytical model of a novel axial reluctance resolver based on finite element method and winding function method is proposed in this paper. The developed resolver is composed of a rotor with half-wave magnetic-bands and a stator with parallel teeth, which can simplify the manufacturing process and convenient for mass production. The anti-interference of the sinusoidal distributed winding configuration is verified using winding function method, and the results of the proposed method under constant and sinusoidal distributed winding configurations are compared with the finite element method in terms of accuracy and computation costs. Additionally, the robustness of the half-wave resolver in the case of axial offset is illustrated and verified with theoretical explanation and numerical simulation. The accuracy of the proposed resolver under healthy and offset conditions are compared and summarized. Compared with the traditional resolver, the half-wave axial reluctance resolver has simpler processing, higher precision and stronger anti-interference. Finally, the results of simulation and the theoretical analysis verified the success of design and analysis processing.